Penatalaksanaan Holistik Penyakit Impetigo pada Anak Usia 12 Tahun di Puskesmas Kampung Sawah melalui Pendekatan Kedokteran Keluarga - deralitha; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2024)
Background: Impetigo is a classification of pyoderma, which attacks the epidermal layer of the skin. Impetigo is divided into two types, namely bullous and non-bullous impetigo. One of the clinical forms most often found in pediatric cases is bullous impetigo, this bacteria spreads from one individual to another through direct contact such as through hand contact. Bullous impetigo has lesions in the form of bullae and has thin walls with reddish edges, most often caused by Staphylococcus aureus. Non-bullous impetigo begins with an erythematous papulovesicle that continues to grow with a yellow crust, most often caused by Staphylococcus aureus and Group A Streptococcus. Objective: Implementing the principle of doctor service according to the problems found and carrying out holistic and comprehensive management including patient-centered and family approaches based on Evidence Based Medicine. Method: This study is a case report. The data obtained include primary data were obtained through alloanamnesis and autoanamnesis, physical examination and home visits and secondary data were obtained from the patient's medical record. Results: Patient girl 12 year old complained of brownish yellow scabs on his face and blisters filled with yellow fluid on his neck. The patient is worried that the complaint is getting worse. Clinically the patient was diagnosed with Impetigo. Next, holistic management is carried out, namely intervention using poster media. In the evaluation, results were obtained in the form of a better understanding of the disease and changes in behavior that had an impact on the success of therapy. Conclusion: The diagnosis and management of this patient has been carried out holistically and comprehensively based on several theories and recent research. In the process of changing behavior, the patient has reached the trial stage.